2018
DOI: 10.1097/md.0000000000011530
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the dynamic contrast-enhanced MRI features and prognostic factors in breast cancer

Abstract: This study analyzed the correlation between the dynamic contrast-enhanced MRI (DCE-MRI) features with prognostic factors of breast cancer. Eighty-five breast cancer patients verified by pathology and immunohistochemistry underwent DCE-MRI examination. Spearman correlation analysis was used to analyze the DCE-MRI features [the strengthening types, shape, distribution, edge, internal reinforcement and the time-signal intensity curve (TIC) types] and the 4 immunohistochemical markers (ER, PR, Her-2, and Ki-67) by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…There was no significant correlation between internal enhancement patterns and the expression of hormonal receptors. This was in concordance with Tao et al [17].…”
Section: Discussionsupporting
confidence: 93%
“…There was no significant correlation between internal enhancement patterns and the expression of hormonal receptors. This was in concordance with Tao et al [17].…”
Section: Discussionsupporting
confidence: 93%
“…1 Dynamic contrast-enhanced (DCE) magnetic resonance imaging (MRI) features can indirectly reflect the tumour proliferation rate and growth of the tumour by providing morphological and kinetic features. 6 Preoperative DCE-MRI of primary breast tumours has the potential to aid prognostic evaluation. 7,8 Several studies have confirmed the prognostic value of DCE-MRI parameters to predict the occurrence of metastasis for breast cancer, and some of these studies have also performed survival analysis.…”
Section: Introductionmentioning
confidence: 99%